Microbiota and metabolite profiles of saliva, oral swab and cancer tissue from patients with oral squamous cell carcinoma (OSCC) - Kailiu Wu; Beihui Xu; Xinyu Zhou; Haiyan Guo; Guanhuan Du; Chenping Zhang; Fuxiang Chen; Xu Chen (Infectious Agents and Cancer)
Abstract Oral squamous cell carcinoma (OSCC) was the most common malignant type of head and neck squamous cell carcinoma (HNSCC) with a low survival rate. The microbiota in oral cavity or tumor tissues may play a critical role in the OSCC. In this study, we characterized the microbiota from oral cancer tissues, oral swabs and saliva of patients with OSCC using 16S rRNA sequencing. We found differential profiles and amounts of microbiota in oral cancer tissues compared with adjacent tissues, as well as in oral swabs and saliva from OSCC patients compared with healthy individuals. Fusobacterium nucleatum and Porphyromonas endodontalis were found increased in cancer tissues and saliva from OSCC patients. Prevotella melaninogenica was found increased in the saliva and oral swabs from OSCC patients. These data suggested that microbiota varied according to different samples. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis indicated an important role of metabolic pathways in the interaction between microbiota and cancers. Then we analyzed the metabolites from cancer tissues and saliva of OSCC patients by liquid chromatograph-mass spectrometry/mass spectrometry (LC-MS/MS) and gas chromatograph-mass spectrometry (GC-MS). Differential profiles of metabolites were also observed in the cancer tissues compared with adjacent tissues and in the saliva from OSCC patients compared with healthy individuals. It showed that denticulaflavonol was significantly increased while D-mannose was significantly decreased in both cancer tissues and saliva of OSCC patients. Taken together, these results suggested an association between microbiota/metabolites (such as Fusobacterium and mannose) and OSCC, in which the molecular mechanism need further investigated.